Sustainable entrepreneurship out of entrepreneurial opportunity identification: The mediating role of psychological capital - Zhang, Hongxin; Chen, Hongxia (Frontiers in Psychology, 2023)
Introduction: Compared with necessity-driven entrepreneurship, opportunity-driven entrepreneurship are more sustainable. Scholars have shown that entrepreneurial opportunity identification (EOI) is key in forming entrepreneurial intention (EI), but little discuss this association with psychological capital (PC). The aim of the present study, in a sample of Chinese university students was to examine the the simultaneous effects of EOI and PC on university students’ EI. Methods: 555 university students in China were enrolled by means of convenience sampling. Descriptive statistics and correlation analysis of variables were performed using SPSS 21.0 software. Structural equation modeling analysis (SEM) with AMOS 21.0 was used to examine the structural effects of EOI and PC on university students’ EI. Results: According to results, university students’ EOI and PC had a positively and insignificantly influence on their levels of EI. Further, PC was found to fully mediate the impact of EOI on EI. Discussion: The present study could shed light on new instructions to examine the interaction between the cognitive and psychological components of EI in the field of entrepreneurship. It is recommended that educators and practitioners should pay regard to the role of EOI and PC.